Spatial design for the Lansdowne Road Corridor - L'Etang, Julia (School of Architecture, Planning and Geomatics, 2014)
The current patterns of urban growth within the city of Cape Town reflect large social inequalities, which is compounded by rapid population growth and urbanisation experienced in the city. The intention of this dissertation is address current socio-spatial inequalities through the management of urban growth, specifically targeted at interventions within the poorest parts of the city through the design of the Lansdowne urban corridor. The theoretical framework for establishing the tools for the management of urban growth are informed by the generic problems with the structure of South African cities, global challenges that face the growth of all cities, and an understanding of what informs the making of spatial plans. An important finding of this is the need for the re-structuring of South African cities to increase integration of historically fragmented areas. The spatial analysis represents the application of the theoretical findings to the context of Cape Town. The analysis is undertaken at a number of scales, to establish the constraints and opportunities present in the area, to inform the spatial design of the corridor area. The intention of the plan is to establish where the investment of direct public funds should occur to generate movement of people within the area, which small scale enterprises can respond to, thus strengthening the conditions for self-sustaining livelihood strategies to occur. An essential part of this requires the restructuring of the existing spatial structure to create a more integrated urban form, which is resolved at the precinct scale.